The Interaction between Teacher and Young Learners at Bilingual Classroom - Dian Rozalia; Sofyan A Gani (Research in English and Education Journal, 2017)
English classroom interaction is a crucial aspect in learning and improving students’ skill. An English teacher communicates actively with the students by using English during the lesson in order to enhance their English skill. This research aims to find out kind of teacher-student communication patterns the 4th grade students of Elementary School at Fatih Bilingual School, one way or two ways communication pattern which is more dominant. The participants of this research were 20 students and an English teacher at 4th grade at Fatih Bilingual School. The data collected were qualitative in nature. The qualitative data were obtained by doing observation, and recording the video to the students and the teacher. The result of this research showed that the percentage of circular interaction is 76% of the total interaction and one way interaction is 24%. Thus, the kind of interaction between the teacher and the students is two way communications (circular) more dominant than one way communication (linear).